Activating people to partner in health and self‐care: use of the Patient Activation Measure. Issue Volume 216:Issue S10(2022)Supplement (5th June 2022) - Janamian, Tina; Greco, Michael; Cosgriff, David; Baker, Laurence; Dawda, Paresh
Summary: Patient activation is a behavioural concept and is at the heart of personalised care. It is defined as an individual's knowledge, skill and confidence for managing their health and health care. Evidence indicates that patient activation scores can predict health behaviour and are closely linked to various clinical outcomes: reduced unnecessary emergency department visits, hospital admissions and re‐admissions. Patients with lower activation levels (25–40% of the population) are less likely to adopt healthy behaviour, and more likely to have poorer clinical outcomes and higher rates of hospitalisation. Effective interventions can improve a patient's activation level, and positive change in activation equates to positive change in self‐care behaviour. But to improve patient activation, we must first measure it using a robust evidence‐based tool such as the Patient Activation Measure (PAM) survey. Armed with the patient's PAM score, providers can tailor their care and help patients achieve better self‐care, which can improve outcomes of care and reduce unnecessary health care utilisation. The PAM is also useful for population segmentation and risk stratification — to target interventions and health strategies to meet the needs of patients who are at different points along the activation continuum, to measure the performance of health care systems, and to evaluate the effectiveness of health care interventions. The role of patient activation requires further serious consideration if we are to improve the long‐term health and wellbeing of all Australians. The PAM tool is a feasible and cost‐effective solution for achieving the Quadruple Aim — improving population health, the cost‐efficiency of the health system, and patient and provider experience.